The default of the municipal savings banks of Peru in the pre and post covid era. Analysis of the microenterprise sector - Bueno Mariaca, Walther Arturo (2022)
COVID-19 has generated economic damage in all the productive sectors of the country. This negative effect resulted in non-compliance in the payment of loans to micro-enterprises, increasing the indicators and default ratio of the so-called intermediary financial entities such as the Municipal Savings Banks in the country. Emphasis is placed on the importance of treating indicators related to the provision of resources to sectors such as microenterprise, the quality of portfolios and how this affects the financial institution. Likewise, this research aims to be able to compare the level of delinquency before and after the pandemic. The research is longitudinal, deductive approach, pure or basic type, relational level and non-experimental design. Regarding the population, it was constituted by information belonging to the Municipal Funds of Peru. The data was obtained from the repository of the Superintendency of Banking, Insurance and AFP and has a monthly periodicity from January 2018 to March 2021. To check and verify the hypothesis of this study, the t statistical test was used for equality of means of independent samples, previously verifying the assumptions of normality and homogeneity of variances. The research concludes that there are differences between delinquency levels before and after covid.